2009
DOI: 10.1016/j.bbi.2008.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic-promoting effects of LPS: Sexual dimorphism and mediation by catecholamines and prostaglandins

Abstract: Inflammation is implicated in several medical conditions that are sexually dimorphic, including depression, cardiovascular diseases, autoimmunity, and presumably cancer progression. Here we studied the effects of the pro-inflammatory agent, LPS, on MADB106 lung tumor retention (LTR), and sought to elucidate underlying mechanisms and sexual dimorphism. F344 male and female rats were administered with LPS (0.001-1 mg/kg i.v.) simultaneously with tumor cell inoculation, and treated with a β-blocker (nadolol, 0.2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 104 publications
(107 reference statements)
2
19
1
Order By: Relevance
“…These findings suggest that female F344 rats are more resilient than males to stress-induced NK suppression in general, and specifically to effects mediated through activation of the SNS. These sexual dimorphisms are consistent with our previous studies employing other stress paradigms [48], and specifically with respect to the impact of β-adrenergic receptor activation on NKCC [54, 55]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings suggest that female F344 rats are more resilient than males to stress-induced NK suppression in general, and specifically to effects mediated through activation of the SNS. These sexual dimorphisms are consistent with our previous studies employing other stress paradigms [48], and specifically with respect to the impact of β-adrenergic receptor activation on NKCC [54, 55]. …”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we have shown that several stress paradigms, or the administration of stress-related factors (catecholamines and their agonists, and prostaglandins), can increase LTR in normal F344 rats, but not in NK-depleted rats, indicating that increased LTR in normal rats under these conditions reflects an in vivo suppression of NK-mediated activity [26, 27]. On the other hand, other manipulations, including surgery or LPS administration [40, 48], increased LTR in both normal and NK-depleted rats, indicating the involvement of non-NK mechanisms in modulating LTR. Thus, the use of this LTR index, in conjunction with an NK-depletion paradigm, can indicate the specific in vivo involvement of NK cells in various manipulations that affect LTR.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the role played by gonadotrophin-releasing hormones (GnRH) and gonadal steroids in sexual differentiation and reproduction, sex hormones are also involved in immune system modulation and development (Tanriverdi et al, 2003;Verthelyi, 2001), as well as playing an important role in brain ontogeny (Harris, 1964). Sexual dimorphism in immune and neuroendocrine responses, driven by reproductive hormonal fluctuations, has been investigated in a number of human and animal studies (Grossman, 1985;Naor et al, 2009). Oestrogen has been shown to attenuate, and testosterone to exacerbate, inflammatory responses in rats (Razmara et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…These findings indicate the involvement of SNS and HPA reactivity in regulating the immunostimulatory effect of CpG-C through the systemic release of CAs and GCs. Stress responses are common in response to several immune-stimulatory agents (e.g., LPS [22]) and in natural responses to pathogens [46], and could constitute a self-limiting mechanism of TLR-9 activation by CpG-C. Interestingly, with respect to CpG-C, we were unable to observe systemic elevated levels of CORT at the time points studied herein and in previous studies in mice [5, 47]. Nevertheless, in vitro physiological CORT levels dose-dependently reduced the efficacy of CpG-C in elevating IL-12 levels.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Opioids were also implicated in immune modulation and were shown to inhibit cellular and humoral immunity, including cytokine production and NK cell activity [21]. It is worthy to note that various types of immune stimulation (BRMs) were reported to induce stress responses, including activation of the SNS and HPA axis [22], which could constitute a negative feedback loop.…”
Section: Introductionmentioning
confidence: 99%